SMARTPHONE SELECTION DECISION SUPPORT SYSTEM BY USING THE WEIGHTED PRODUCT METHOD - Andi Fauziah Yahya; Rafly Putratama Fitri; Jumaldi Jumaldi; Andi Hutami Endang (SEAN Institute, 2022)
Smartphone has become a must-have device that is essential and integral part of life. It is no longer a luxury commodity but a basic life necessity for millions of people. Various brand and models of smartphones provide customers several options yet create dilemma when deciding the one to purchase. The research objective is to provide decision support system in order to assist customer in decision making process for purchasing smartphones. This research applied a quantitative approach with Weighted Product Method analysis. Purposive sampling technique was chosen as the method of determining respondents. The data obtained through questionnaire from 45 students of Kalla Institute Technology and Business. Based on the research analysis using Weighted Product method, the most recommended smartphone to buy is Iphone from Apple.